From Ethnic Prejudice to Employment Discrimination: The Role of Small Firms as Mediators - Gabor Kertesi; János Köllő; Róbert Károlyi; Lajos Tamás Szabó (Institute of Labor Economics (IZA), 2025)
Hungary's sizeable Roma minority is hit by massive prejudice. Using 2011 Census data and supplementary sources, we study how ethnic bias translates to employment discrimination in local labor markets. The male ethnic employment gap, adjusted for a rich battery of controls, was 20-40 percent wider than average if, and only if, the local population strongly supported an openly anti-Roma far-right party and, at the same time, small firms had a substantial share in the local economy. Roma women's (very low) employment is less responsive to prejudice and the small firm share. The results for men, the sole breadwinners in most Roma families, survive robustness checks and confrontation with alternative explanations. Since small firms easily elude the anti-discrimination regulations, the results draw attention to the limits of legal instruments and call for active policy.
Keywords: J15; J71; R23; D22; 330; minorities; discrimination; regional labor markets; small firms